2023
DOI: 10.35848/1347-4065/accc93
|View full text |Cite
|
Sign up to set email alerts
|

Development of diagnostics of electron density and temperature for atmospheric-pressure helium plasma based on optical emission spectroscopy analysis and a collisional-radiative model

Abstract: An algorithm for diagnosing the electron density and temperature of helium plasma at atmospheric pressure has been developed based on a revised helium collisional-radiative (CR) model. Atomic collision processes are included and part of the atomic data of electron collision processes in the conventional CR model has been updated to expand its valid pressure. The algorithm uses eight emission lines in the visible-wavelength range as inputs to determine the electron density, electron temperature, and number dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Hence, in order to confirm the potential of the method of OES measurement of continuum emission and the specific precautions to be taken when implementing it, the author's group also launched experimental research and confirmed the effectiveness of this method through various measurements and cross-checks. 57,[60][61][62] The author's group have been studying with validity examination whether the EEDF should be Maxwellian, Druyvesteynian, or something else. The author is also proposing mathematical methods to presume the arbitrary EEDF from the observed continuum emission as remarkable issues with originality.…”
Section: Measurement Of Electron Temperature and Density Using Contin...mentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, in order to confirm the potential of the method of OES measurement of continuum emission and the specific precautions to be taken when implementing it, the author's group also launched experimental research and confirmed the effectiveness of this method through various measurements and cross-checks. 57,[60][61][62] The author's group have been studying with validity examination whether the EEDF should be Maxwellian, Druyvesteynian, or something else. The author is also proposing mathematical methods to presume the arbitrary EEDF from the observed continuum emission as remarkable issues with originality.…”
Section: Measurement Of Electron Temperature and Density Using Contin...mentioning
confidence: 99%
“…The strategy for spectral analysis is to obtain the continuum spectrum of electron-atomic bremsstrahlung obtained as shown in Fig. 14, using T e and N e in the theoretical equation as best fitting parameters, 57,60) which will be described in this chapter in detail.…”
Section: Measurement Of Electron Temperature and Density Using Contin...mentioning
confidence: 99%
See 2 more Smart Citations